PENINGKATAN PEMBELAJARAN SEPAK BOLA DENGAN MEMANFAATKAN PERKEBUNAN SENGON BAGI SISWA KELAS VII C SMP N 1 PLANTUNGAN KABUPATEN KENDAL TAHUN PELAJARAN 2012/2013 (Department of Physical Education, Sport, Health and Recreation, 2015)
This study aims to improve learning outcomes by utilizing plantation football sengon for Junior High School students in the learning of Physical Education , Sport and Kesehatan.Penelitian using action research methods . The subjects were class VII C SMP N 1 Plantungan , District Plantungan , Kendal . Of the 112 students , only 28 samples were used in the retrieval of data students obtained from observations at the time of learning , performance test and written test results, the results siswa.Berdasarkan percentage of mastery learning in the first cycle , 32.14 % psychomotor aspect , affective aspect 57 % and 96.4 % increases the cognitive aspects of the second cycle increased psychomotor aspects 79 % , 86 % and affective aspects of the cognitive aspects of 100 % . Learning outcomes in the first cycle to meet the KKM much as 67.9 % of the total number of students in the second cycle and increased to 87.5 % of the total siswa.Berdasarkan the above results , it can be concluded that learning football by utilizing plantation sengon can improve learning outcomes soccer on class VII C SMP N 1 Plantungan.